O sertanejo e o sevilhano nos poemas de João Cabral de Melo Neto: o lusco-fusco barroco - Vinagre, Verônica Falcão de Oliveira (2014)
The aim of this research is, starting from a Baroque reading, unfold the understanding of the poems by João Cabral de Melo Neto in the axis Pernambuco-Spain. From this perspective, the reading of poet s Obra Completa allows the appearance of two persons, one from Seville and other from the Brazilian countryside, whom curiously pulsate and reveal themselves from their homelands, Brazilian northeastern dry lands and Seville, to a labyrinthy meeting establishing a close and exciting relationship of cities apart but which mark a contiguous dialogue between both cultures. The theorical effort of this investigation permeates, approaches and contrasts the directions of, among others, Severo Sarduy (1999), Gilles Deleuze (2012) and Eugenio D Ors (unknown). Not traveling an anthropological bias, this study observes the Spanish space and the Brazilian northeastern dry lands space, joining the regional to the universal and analyzes the baroque game in the (re) construction of the both men s cultures. These elements fuse, approach and move away, causing a game of allusions to Pernambuco and Spain that show itself through a similar cultural bias and different at the same time. From this apprehension it is possible to understand the synthesis of the Brazilian arid northeast-Seville men as a update of seventeenth century Baroque coming from indexes that are shown over the particular written by João Cabral de Melo Neto, in the Iberian Baroque scenario and in the American one s